Grammatical Cohesion in Durūsul Lugah Volume 1 and Its Implications for Arabic Language Learning - Rostiani, Yeni; Nuriah, Zahroh (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Based on Halliday and Hasan's (1976) theory, this study looks at how the four grammatical devices of cohesion are used in Durʫsul Lugah Volume 1: reference, substitution, ellipsis, and conjunction. We used a descriptive qualitative approach to collect data, employing the reading, listening, and note-taking technique. The data analysis involved data reduction, presentation, and conclusion. The results show that conjunction and reference appear in almost every chapter, while substitution and ellipsis only begin to emerge in the later chapters. However, the variety within each type of cohesion remains limited. These findings have implications for teaching Arabic. For example, they can help students better understand the additive and adversative meanings of the word "and," give clear instructions on word forms and types, and better understand pronouns (ḍamīr). We also encourage learners to enhance their linguistic awareness. Overall, the types of grammatical cohesion in Durūsul Lugah Volume 1 are not yet highly diverse. However, the book's text maintains grammatical coherence, making it suitable for beginner-level Arabic learners.